2021
DOI: 10.1021/acs.iecr.1c00089
|View full text |Cite
|
Sign up to set email alerts
|

Study of Liquid–Solid Mass Transfer and Hydrodynamics in Micropacked Bed with Gas–Liquid Flow

Abstract: The volumetric liquid–solid (L-S) mass transfer coefficient under gas–liquid (G-L) two-phase flow in a silicon-chip-based micropacked bed reactor (MPBR) was studied using the copper dissolution method and was related to the reactor hydrodynamic behavior. Using a high-speed camera and a robust computational image analysis method that selectively analyzed the bed voidage around the copper particles, the observed hydrodynamics were directly related to the L-S mass transfer rates in the MPBR. This hydrodynamic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Krishnamurthy et al 31 proposed the bubbly slug, gas slug, bridged, and annular flow regimes in the μPBR by their studies. Cao et al 39 displayed the liquid‐dominated slug, sparse slug, and gas continuous with pulsing flow regimes in the μPBR. The gas and liquid superficial velocities in Krishnamurthy et al 31 and Cao et al 39 studies were at least two or three orders of magnitude higher than that of other studies, which represented the flow behaviors of the μPBR in the extreme situations.…”
Section: Resultsmentioning
confidence: 99%
“…Krishnamurthy et al 31 proposed the bubbly slug, gas slug, bridged, and annular flow regimes in the μPBR by their studies. Cao et al 39 displayed the liquid‐dominated slug, sparse slug, and gas continuous with pulsing flow regimes in the μPBR. The gas and liquid superficial velocities in Krishnamurthy et al 31 and Cao et al 39 studies were at least two or three orders of magnitude higher than that of other studies, which represented the flow behaviors of the μPBR in the extreme situations.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, new methods for measuring solid–liquid mass transfer have also been reported, , such as limiting current electrochemical technique and so forth. However, the obtained Sh in the traditional STR is usually less than 100 where the obtained k S is in a low level. , …”
Section: Introductionmentioning
confidence: 99%
“…Mass transfer studies, as one of the crucial parts in fundamental researches, were the hotspots in the realm of reactor design, which was beneficial for the cognitive enhancement and better understanding of the scaling‐up processes 14–16 . Several mass transfer studies have been carried out in the μPBRs, including gas–liquid, liquid–solid, and gas–liquid–solid systems.…”
Section: Introductionmentioning
confidence: 99%
“…13 Mass transfer studies, as one of the crucial parts in fundamental researches, were the hotspots in the realm of reactor design, which was beneficial for the cognitive enhancement and better understanding of the scaling-up processes. [14][15][16] Several mass transfer studies have been carried out in the μPBRs, including gas-liquid, liquid-solid, and gas-liquid-solid systems. Losey et al 17 evaluated mass transfer in the μPBR within Pt/Al 2 O 3 catalyst by cyclohexene hydrogenation reaction and showed that overall mass-transfer coefficients were two orders of magnitude larger than that of the conventional packed bed.…”
Section: Introductionmentioning
confidence: 99%